2011
DOI: 10.1002/lapl.201110098
|View full text |Cite
|
Sign up to set email alerts
|

Functional planar thin film optical waveguide lasers

Abstract: Fabrication and characterization of planar and channel waveguiding thin films with the goal to develop active and passive elements are intensively studied over the last 20 years. Large scale of materials and properties were tested (morphology, crystallinity, luminescence, waveguiding, etc.). The goal of our contribution is to give an overview of materials and fabrication processes which were used for development and construction of functional planar waveguide lasers (PWL). The compact survey of finalized PWL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The calculations for determining applied threshold fluence (φ th ) and (φ 0 ) are obtained according to the method of Liu et al [27]. The spatial fluence, (φ(r)) for a Gaussian beam is given by: …”
Section: Fabrication Of a Cell Electrostimulator Using Pulse Laser Dementioning
confidence: 99%
See 1 more Smart Citation
“…The calculations for determining applied threshold fluence (φ th ) and (φ 0 ) are obtained according to the method of Liu et al [27]. The spatial fluence, (φ(r)) for a Gaussian beam is given by: …”
Section: Fabrication Of a Cell Electrostimulator Using Pulse Laser Dementioning
confidence: 99%
“…In some cases, it could be the synthesis of a thin-film material or structure [25]. In other cases, the research focused in the development of specific devices, such as in the growth of nitride films in the development of LED devices or in the fabrication of thin waveguiding films [26,27]. PLD has also proven to be very effective in the growth of crystalline oxides, [28] or PLD-grown of high-temperature superconducting films (HTS), whose applications include high-frequency electronics for radio frequency, microwave communications, and superconducting quantum interference devices (SQUIDs) for the detection of magnetic fields [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore utilizing waveguides with low propagation losses in comparison with the small signal gain coefficient is critical. Developing practical fabrication methods for low-loss PWs continues to be a challenge and an active area of research, for which direct bonding and epitaxial growth have shown the greatest promise for single or multi-layer crystalline waveguides [9]- [12]. In recent years several efficient crystalline waveguide lasers have been reported based on channels defined by direct writing techniques imposing stress-induced near-single-mode cores within a bulk crystalline host [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of Δn = 0, the "inner cladding" and doped core have the same refractive index essentially resulting in a single-clad waveguide with the active ions confined to a "core" layer of thickness less than the distance between the "outer cladding." Considering the geometry of the PW, there are two practical generic configurations for exciting the active region, face pumping or in-plane pumping, of which the latter can be either from the side (transverse) or end (longitudinal) [9], [12]. All three pumping orientations have been used to good effect in producing high power lasers: with face pumping employing relatively straightforward multi-pass pump cavities to enhance the absorption in the core region [18], [27], whereas direct "singlepass" excitation is achieved by side pumping [19], [28]- [30], or end-pumping [31]- [36].…”
Section: Introductionmentioning
confidence: 99%